Polarized wnt signaling regulates ectodermal cell fate in Xenopus - Huang, Ya-Lin; Niehrs, Christof (Developmental cell, 2014)
How cells convert polarity cues into cell fate specification is incompletely understood. Here, we show that Wnt/β-catenin and Wnt/PCP signaling cooperate in this process in early Xenopus embryos. We find that the Wnt coreceptor Lrp6 is asymmetrically localized to the basolateral membrane in ectodermal blastomeres. Lrp6 asymmetry is controlled by Wnt/PCP signaling, indicating that this pathway regulates not only planar- but also apicobasal cell polarity. Following asymmetric cell division, Lrp6 preferentially sorts to the deep ectodermal cell layer and becomes depleted in the epithelial cell layer. This is accompanied by elevated Wnt/β-catenin signaling in deep cells, which in turn promotes their differentiation into ciliated cells. We conclude that coordinated Wnt/PCP and Wnt/β-catenin signaling convert apicobasal polarity information to specify ectodermal cell fate.
Gesehen am 12.01.2021